Otimização de estruturas treliçadas geometricamente não lineares submetidas a carregamento dinâmico - Martinelli, Larissa Bastos (2019)
This study addresses the optimization of lattice structures with geometrically nonlinear behavior under dynamic loading. The formulated optimization problem aims to determine the cross-sectional area of the bars which minimizes the total mass of the structure, imposing constraints on nodal displacements and stresses. In order to solve this optimization problem, it was developed a computational program on MATLAB®, using the Interior Point method and the Sequential Quadratic Programming method, the algorithms of which are available on Optimization Toolbox™. It was included routines for grouping the bars and to convert the optimal solution obtained using continuous design variables in commercial values of structural hollow-sections. The space truss nonlinear finite element is described by an updated Lagrangian formulation. The implemented geometric nonlinear dynamic analysis procedure combines Newmark’s method with Newton-Raphson type iterations, being validated by comparison with solutions available in the literature and with solutions obtained using ANSYS® software. Examples of plane and space trusses under different dynamic loading are solved using the developed computational program. The results show that: the Sequential Quadratic Programming method is the most efficient to solve the studied optimization problem, consideration of structural damping can lead to a significant reduction in the total mass, the use of the conversion procedure for commercial sections provides solutions in favor of security and the grouping of bars generates a satisfactory duration for the optimization process.